Condition-specific health-related quality of life amongst amateur athletes six months and one-year following sport-related concussion: A prospective, follow-up. (September 2021) - Büttner, Fionn; Howell, David R.; Doherty, Cailbhe; Blake, Catherine; Ryan, John; Delahunt, Eamonn
Abstract: Objective: To prospectively investigate the condition-specific health-related quality of life (HRQoL) of athletes six months and one-year following sport-related concussion. Design: Prospective, longitudinal study. Setting: Clinical research centre at university school of public health. Participants: Amateur athletes who were diagnosed with sport-related concussion within one-week after presenting to a hospital emergency department were recruited along with sex-, age-, and activity-matched, non-concussed, control athletes. Concussion and control participants were assessed six months and one-year following sport-related concussion and study enrolment, respectively. Main outcome measures: Participants completed the Post-Concussion Symptom Scale and five condition-specific HRQoL patient-reported outcome measures – Headache Impact Test-6, Fatigue Severity Scale, Neck Disability Index, Generalised Anxiety Disorder-7, and Dizziness Handicap Inventory. We performed Frequentist and Bayesian mixed-design analyses of variance to compare the concussion group and control group at both assessments and quantify whether there was greater evidence in favour of the null hypothesis compared with the alternative hypothesis. Results: At six-month and one-year assessments, the concussion group (n = 47; male = 72%; mean (SD) age = 22.68 (5.07)) and the control group (n = 47; male = 72%; mean (SD) age = 23.81 (4.60)) reported similar clinical symptom severity scores and condition-specific HRQoL. The proportion of athletes in the concussion group with clinically-impaired scores was similar to the proportion of non-concussed athletes with clinically-impaired scores. At six-month and one-year assessments, there was moderate-to-very strong evidence that there was no difference between concussion and control participants' perceptions of the effects of headache, fatigue, neck pain, anxiety, and dizziness on HRQoL. Conclusion: There was moderate-to-very strong evidence in favour of no difference between the concussion and control groups on symptom severity scores and condition-specific HRQoL patient-reported outcome measures at six-month and one-year assessments. These results suggest that condition-specific HRQoL returns to the levels of non-concussed individuals within six months following sport-related concussion. Highlights: At six months and one year, concussed athletes reported similar clinical symptoms and HRQoL versus non-concussed athletes. The proportion of concussed athletes and control athletes with clinical HRQoL at six months and one year was similar. These findings support prior work suggesting HRQoL normalises for most athletes within six months after sports concussion.